Lack of association between TNF-308 polymorphism and the clinical and immunological characteristics of systemic lupus erythematosus and primary Sjögren's syndrome (2005)
Objective: To investigate the previously reported association of tumor necrosis factor alpha (TNF) -308 single nucleotide polymorphism (SNP) with the clinical course and immunological features in patients with systemic lupus erythematosus (SLE) and primary Sjögren's syndrome (pSS). Methods: The studied group consisted of 113 consecutive SLE and 65 pSS patients. TNF -308 SNP was determined by the polymerase chain reaction-restriction fragment length polymorphism technique. Clinical and immunological characteristics were assessed according to a standard protocol that included disease activity (SLEDAI) and damage (SLICC Damage Index). Serum TNF? levels were measured in samples collected from 32 patients with SLE and 16 with pSS by enzyme-linked immunosorbent assay. Results: The TNF2 allele (A) was observed in 46% and 54% of SLE and pSS patients, respectively. We failed to find any significant association between the -308 SNP and disease manifestations, the presence of autoantibodies or cytokine levels in either group. Conclusion: TNF -308 SNP (TNF2) does not exhibit a significant influence on the disease course or immunological response in SLE and pSS. Other genetic and/or environmental factors seem to be required and to be more important than TNF2 allele for the progression of these diseases.